Economic cycles and punishment: unemployment and imprisonment - Laffargue, Bernard (Contemporary crises, 1989)
Research on the relations between the labor market and forms of punishment, inaugurated by Rusche, has developed along two lines, broadly speaking: first, the historical evolution of the links between the structure of the labor market and the structure of punishment and secondly, the conjunctural variations in admissions to prison and in prison populations with fluctuations in the employment situation. The present study is of the latter type. It stems from observations on two aspects of the French situation: The concomitant long-term evolution (1875-1985) of curves for unemployment and for prison populations, given the downward trend in imprisonment rates until recent years. - The constant over-representation, among prisoners, of groups whose position on the labor market is insecure. The link between unemployment and imprisonment was tested by multiple regression using data on economic, demographic, penal and correctional aspects (French figures, 1920-1985). The results show the participation of demographic factors in the variations in prison populations. They point to a significant correlation between variations in unemployment (in volume and rate) and the evolution of prison populations, all else being equal in terms of recorded crime.Analysis of the functioning of the criminal justice system, showing the existence of an internal subsystem characterized by its procedures - pretrial detention -, the offenses - street crime -, the sentences - imprisonment - and the social characteristics of those convicted, suggests an approach to the interpretation of these findings.